2008
DOI: 10.1519/jsc.0b013e31815f958d
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of Heavy Back and Front Squats on Speed during Forty-Meter Sprint Trials

Abstract: The purpose of the present study was to investigate the effects of performing heavy back squats (HBS) and heavy front squats (HFS) on the average speed during each 10-m interval of 40-m sprint trials. In a randomized, cross-over design, 10 strength-trained men performed a HBS, HFS, or control treatment before performing three 40-m sprint trials separated by 3 minutes. The HBS and HFS treatments consisted of performing parallel back or front squats with 30%, 50%, and 70% of the subject's 1 repetition maximum af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 8 publications
2
64
0
5
Order By: Relevance
“…The strength exercises commonly used have tended to be bilateral, which may provide limitations as to biomechanical specificity [16,17], although the preload intensity can be delivered. For example, parallel back squats performed with 30-70% 1RM were found to potentiate the 10-20 m and 30-40 m intervals of a 40-m sprint after 4 minutes (min) in strength-trained men [16], while loads of 85% [13] and 90% [18] of 1RM improved 40-m sprint time after 4 min in soccer and Division III football players, respectively. When recovery periods were individualized in professional rugby players, Bevan et al [19] found 0-5 m and 0-10 m sprint times were potentiated by 3 back squats performed with 91% of 1RM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strength exercises commonly used have tended to be bilateral, which may provide limitations as to biomechanical specificity [16,17], although the preload intensity can be delivered. For example, parallel back squats performed with 30-70% 1RM were found to potentiate the 10-20 m and 30-40 m intervals of a 40-m sprint after 4 minutes (min) in strength-trained men [16], while loads of 85% [13] and 90% [18] of 1RM improved 40-m sprint time after 4 min in soccer and Division III football players, respectively. When recovery periods were individualized in professional rugby players, Bevan et al [19] found 0-5 m and 0-10 m sprint times were potentiated by 3 back squats performed with 91% of 1RM.…”
Section: Introductionmentioning
confidence: 99%
“…For example, only Bevan et al [19] illustrated that 10-m sprint performance can be potentiated by a strength exercise. Numerous other studies have illustrated that speed over distances less than 20 m were not potentiated by a strength-based conditioning activity [10,15,16,18,20,21]. Yetter and Moir [16] stated that an exercise such as a back squat may not provide a movement-specific stimulation to the muscles required for sprint acceleration due to the different mechanical demands of acceleration versus maximal velocity sprinting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted, it is stated that there is a significant difference between the best sprint timing and sprint average values at the protocol performed in the forms of a one-set-five-repetition exercise with %50 of 1RM, a three-repetition exercise with %70 of 1RM, and a five-set-one-repetition exercise with %90 of 1RM (Okuno et al, 2013). Unlike the above studies, Yetter & Moir (2008), determine that the front squat does not increase the sprint performance but the back squat provided faster sprint speeds in 10-20 m and 30-40 m while it does not provide this in 0-10 m and 20-30 m. Besides, these studies do not support our study; it is also different from our study in terms of the participants who are not elite athletes.…”
Section: Discussionmentioning
confidence: 95%
“…We choose the BSQ for two primary reasons. Firstly, the BSQ has been used successfully in prior research as a potentiating exercise for increasing sprint speed [21]. Secondly, the BSQ is a closed chain, full body, multi-joint exercise known for its ability to place "controlled stress on the musculoskeletal system" [22].…”
Section: Discussionmentioning
confidence: 99%